2014
DOI: 10.1017/s2040174413000548
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of maternal perinatal undernutrition are lowered by cross-fostering during lactation in the male rat

Abstract: Undernutrition exposure during the perinatal period reduces the growth kinetic of the offspring and sensitizes it to the development of chronic adult metabolic diseases both in animals and in humans. Previous studies have demonstrated that a 50% maternal food restriction performed during the last week of gestation and during lactation has both short- and long-term consequences in the male rat offspring. Pups from undernourished mothers present a decreased intrauterine (IUGR) and extrauterine growth restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Taken together, these results provide new information in milk composition from young undernourished rat mothers (60 days old). Although milk production was not directly measured in the present study, several arguments suggest that maternal perinatal undernutrition also decreases milk quantity: 1) milk from undernourished mothers is more concentrated and thus less hydrated, reflecting a reduction of milk volume; 2) cross-fostering of control pups by undernourished mothers also led to reduced kinetic of growth, whereas FR50 pups nursed by control mothers exhibited a weight gain similar to control pups, suggesting that maternal nutrition does not modify feeding behavior in rat neonates (53); and 3) lactose, the main sugar in most mammalian species, is reduced in the milk of undernourished mothers. It is known to be the primary osmotic agent that attracts water in the milky secretion, and is thus considered as the major determinant of milk volume (36).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Taken together, these results provide new information in milk composition from young undernourished rat mothers (60 days old). Although milk production was not directly measured in the present study, several arguments suggest that maternal perinatal undernutrition also decreases milk quantity: 1) milk from undernourished mothers is more concentrated and thus less hydrated, reflecting a reduction of milk volume; 2) cross-fostering of control pups by undernourished mothers also led to reduced kinetic of growth, whereas FR50 pups nursed by control mothers exhibited a weight gain similar to control pups, suggesting that maternal nutrition does not modify feeding behavior in rat neonates (53); and 3) lactose, the main sugar in most mammalian species, is reduced in the milk of undernourished mothers. It is known to be the primary osmotic agent that attracts water in the milky secretion, and is thus considered as the major determinant of milk volume (36).…”
Section: Discussionmentioning
confidence: 57%
“…Breast milk is known to contain many bioactive factors (2) involved in the development and growth as well as in the maturation of the immune system and gut microbiota (13,27). We have recently shown that cross-fostering by control mothers of IUGR pups prevents the development of hyperphagia, hypertension, and intolerance to glucose observed in perinatally food-restricted adult male rats (53). Interestingly, maternal nutritional status during lactation influences leptin concentration both in milk and in the plasma of pups (53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested the compensatory effects of prenatal undernutrition with adequate postnatal nutrition or hormonal therapy (Reynolds et al 2013;Wattez et al 2014), whereas other authors remain quite pessimistic. Animal research shows that a spare diet from a young age might be helpful in preventing age induced damage on pancreatic β cells (He et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal protein restriction leads to sympathetic overactivity and oxidative dysfunction at the medulla oblongata of Wistar rat dams [54]. There is an increase in circulating leptin in the adult offspring [55]; leptin can stimulate the sympathetic nervous system in rodents [56•]. Chronic administration of leptinin humans does not increase BP [56•].…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%